Governance of China’s Periphery: Balancing Local Autonomy and National Unity - Potter, Pitman B. (Columbia Journal of Asian Law, 2005)
China’s governance of its peripheral areas has historically been a matter of national identity and remains so today. In keeping with its Marxist-Leninist heritage, the People’s Republic of China (“PRC”) has viewed the periphery in policy terms-initially as a challenge for socialist transformation and more recently as a locus of economic development. China depicts itself as a unitary state. The continued influence of Confucian patrimonial sovereignty along with concerns over national unity, wealth, and power has supported ideas and practices of governance that remain hierarchical and authoritative. As China’s participation in the world political economy has exposed liberal governance regimes, the dynamics of selective adaptation continue to adjust these to China’s official norms of centralized governance. Yet Chinese and foreign observers frequently point to the extent of local resistance to central government rule. This is particularly true around the periphery, where tensions between central authority and local resistance are especially acute. While governance regimes for the periphery have generally been tailored to reflect the policy priorities of the Chinese Communist Party (“CCP”), the past ten years have seen increased public reliance on legal forms to formalize and lend legitimacy to policy preferences. In light of nearly thirty years’ experience with other dimensions of China’s legal system, it is appropriate and important for us to consider the extent to which rule of law ideals are realized in China’s approach to governance in the sensitive peripheral regions. Accordingly, this paper will examine the legal regime for China’s governance in the Inner Periphery areas of Inner Mongolia, Xinjiang, and Tibet in light of the dynamics of institutional capacity and the implications for China’s relations with the Outer Periphery areas of Macao, Hong Kong, and Taiwan.